2015
DOI: 10.1007/s00497-015-0261-7
|View full text |Cite
|
Sign up to set email alerts
|

A decade of pollen transcriptomics

Abstract: Key messageOverview of pollen transcriptome studies.Pollen development is driven by gene expression, and knowledge of the molecular events underlying this process has undergone a quantum leap in the last decade through studies of the transcriptome. Here, we outline historical evidence for male haploid gene expression and review the wealth of pollen transcriptome data now available. Knowledge of the transcriptional capacity of pollen has progressed from genetic studies to the direct analysis of RNA and from gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
104
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 126 publications
(107 citation statements)
references
References 149 publications
(211 reference statements)
3
104
0
Order By: Relevance
“…Despite this limitation, the ease of experimental setup and noninvasive nature of the technique argue for this approach, which does not require the extensive postharvesting purification steps required for alternative biochemical approaches such as TRAP-seq (Lin et al, 2014;Kim et al, 2015) or isolation of nuclei tagged in specific cell types (INTACT; Deal and Henikoff, 2011). Our analysis of Cvi x Col cross-pollinations revealed that ;8% of pollinated A. thaliana pistil RNA is derived from the pollen tube and we found strong correlations between our analysis and previous microarray analyses of the component cell types (microarray experiments recently reviewed in Rutley and Twell [2015]; Figure 2). Importantly, we identified hundreds of novel pollen tube-and pistil-expressed genes and showed that SNP-informed RNA-seq analysis of pollination can be used to identify promoter elements that drive gene expression in the pollen tube in response to growth through the pistil (Figure 4).…”
Section: Discussionsupporting
confidence: 64%
“…Despite this limitation, the ease of experimental setup and noninvasive nature of the technique argue for this approach, which does not require the extensive postharvesting purification steps required for alternative biochemical approaches such as TRAP-seq (Lin et al, 2014;Kim et al, 2015) or isolation of nuclei tagged in specific cell types (INTACT; Deal and Henikoff, 2011). Our analysis of Cvi x Col cross-pollinations revealed that ;8% of pollinated A. thaliana pistil RNA is derived from the pollen tube and we found strong correlations between our analysis and previous microarray analyses of the component cell types (microarray experiments recently reviewed in Rutley and Twell [2015]; Figure 2). Importantly, we identified hundreds of novel pollen tube-and pistil-expressed genes and showed that SNP-informed RNA-seq analysis of pollination can be used to identify promoter elements that drive gene expression in the pollen tube in response to growth through the pistil (Figure 4).…”
Section: Discussionsupporting
confidence: 64%
“…Angiosperm species apart from Arabidopsis and rice are scarce (Rutley and Twell, 2015), a 526 mere comparison of these two species indicates that the EXO70C class is most probably 527 related to pollen tube development in all Angiosperms, suggesting conservation of the 528 EXO70C expression across monocots and dicots (Add. File 8 in Wei et al, 2010).…”
Section: Exo70c2 Involvement In the Cell Wall Deposition 432mentioning
confidence: 99%
“…During the last decades, the number of studies focused on the haploid male gametophyte significantly increased, accompanied by the evolution and the spreading of molecular techniques (Feng et al 2013;Honys and Twell 2004;Rutley and Twell 2015;Twell 2011;Wang et al 2008;Wei et al 2011). Querying a reference scientific literature database such as PubMed (http://www.ncbi.nlm.nih.…”
Section: Current Research For Pollenmentioning
confidence: 99%